Research-inquiry activities: following tracks of microorganisms at school. (3rd July 2021) - Dönmez, İsmail
Abstract: Bacteria, viruses, and other invisible creatures are, in brief, microorganisms. Especially with the onset of the COVID-19 pandemic, the features of microorganisms, their density, and relevant precautions have grown in importance. Knowing the density of microorganisms at school will cause our cleaning habits to change. In this study, efforts were made to determine the density of microorganisms in a school with an inquiry-based model. In the activity, students were divided into groups and traced microorganisms in different environments of the school using blood agar, swabs, and gloves. At the end of the activity, it was observed that the students had learned about the properties and density of bacteria and the precautions to be taken. In the course of this research, a rubric was developed that can be used for students with the "predict, observe, explain" technique.